Design of an automatic headlight switch for car - Lau, Alex, Sie Bing (2008)
This project is focus on constructing an automatic headlight switch for car. The circuit is operating base on the amount of light entering the phototransistor to activate the system. The main hearts of the circuit are phototransistor and electromagnetic relay. A phototransistor is used as a light detector and relay is used as a switch to switch between high beam and low beam. A measurement of the light intensity during night time at Kota Kinabalu area has been carried out. After analysis has been done, the suitable light intensity for the switch to operate is determined. The suitable light intensity for the switch to operate is at 12 lux. Finally the automatic headlight switch circuit is built and the sensor circuit is operating at 12 lux with the response time of (O.637±O.OO 1) s. The headlight switched from high beam to low beam when amount of light received is higher than 12 lux. The light received may include the light from street lamps, buildings, and cars. When the condition at road is dar~ which is lower than 12 lux, the car headlight will automatically switch from low beam to high beam.